Implementing Differentiated Learning for Children with Special Needs in Islamic Early Childhood Education - Irmayani, Ira; Mahabbati, Aini (Papanda Publisher, 2025)
Early childhood education faces increasing challenges in accommodating children with special needs, requiring adaptive instructional approaches that address diverse learning requirements. This study examines the implementation of differentiated learning strategies for children with special needs in Islamic early childhood education settings. A descriptive qualitative study was conducted at Pesantren Anak Sholeh Baitul Quran Gontor Sangatta from February to April 2025. Data collection involved semi-structured interviews with three teachers and classroom observations focusing on children with ADHD and hearing impairments. The study examined differentiation across content, process, product, and environmental dimensions using triangulation and prolonged engagement for data validity. Teachers successfully implemented differentiated learning strategies across all four dimensions. For children with ADHD, strategies included visual media utilization, graduated instruction delivery, physical activity integration, and strategic seating arrangements. For children with hearing impairments, adaptations emphasized visual learning supports, gestural communication, slowed instruction pace, and front-row positioning. Teachers demonstrated flexibility in assessment approaches, allowing creative expression through drawing, crafting, and storytelling rather than traditional written formats. The findings align with contemporary differentiation frameworks and support theories emphasizing executive function support and cognitive load management. Implementation challenges included resource limitations and the need for enhanced teacher preparation. The study contributes empirical evidence for differentiated learning effectiveness in Indonesian Islamic educational contexts while highlighting the importance of systematic adaptations for inclusive education.